Protecting the learning space: The case for the regulation of staff-student relationships at university campuses in South Africa - Omar, J. (South African Journal of Higher Education, 2019)
Concern over sexual violence at South African higher education institutions has been mounting since 2012. The systemic inquiry into sexual harassment at the University of the Witwatersrand that looked into the patterns, prevalence and problems in regulating sexual harassment at the campus, found that sexual harassment is prevalent and manifests in a number of different ways. In 2016, students at Rhodes University publicised a list of names of alleged sexual offenders at the university (Seddon 2016). The Department of Higher Education and Training has developed a working document, the Draft policy and strategic framework 2017, which seeks to provide a framework for universities and Technical and Vocational Education and Training (TVET) colleges to deal with sexual harassment and sexual offences on campus (Department of Higher Education and Training 2017). It is useful to use the moment of this national debate to highlight the often-ignored issue of sexual relationships between staff and students. This article will consider the merits of regulating these relationships, and how regulation can facilitate mechanisms for accountability and a healthy teaching and learning environment.